A detailed research on the structural characteristics of Hoang Sa and Truong Sa archipelagos - East Vietnam Sea based on gravity data analysis - Dung, Nguyen Kim; Thanh, Do Duc; Vuong, Hoang Van; Cuong, Do Huy; Dung, Tran Tuan; Dai, Nguyen Ba; Duong, Tran Tuan (Vietnam Journal of Marine Science and Technology, 2019)
The Hoang Sa and Truong Sa archipelagos are the two archipelagos located in the East Vietnam Sea. In the geographic coordinate frame, the Hoang Sa archipelago is located more northward than the Truong Sa. Up to now many publications have discussed in detail structures of these archipelagos in terms of international and domestic scientific journals, the scientific workshop reports, as well as the outcome reports obtained from the research projects of different levels, such as state and ministry level projects. However the block characteristics of the two archipelago regions are still in controversy. By application of the new technique (Curvature Gravity Gradient Tensor - CGGT) for analysis and collection of the related available data, some new information about structural characteristics of the two blocks, such as their spatial distribution, the penetration of their boundaries and fault systems was obtained. According to the results, block characteristic is clearly reflected as a unique structural unit for Hoang Sa archipelago, which occupies a large area restricted mostly by the geographic coordinate frame: 111.2oE–113.2oE and 15.75oN–17.25oN. Here a large negative Hoang Sa structural block with the density less than 2.67 g/cm3 develops directly on a more negative regional structure. Unlike Hoang Sa block, the Truong Sa archipelago is not presented as a unique block. Its structure is divided into 3 main smaller blocks distributed along different directions. The first north - south structural block consists of a number of islands and sandbars: Dinh Ba, Song Tu Dong island, Song Tu Tay island, Thi Tu island, Ba Binh island, Ca Nham sandbar, Loai Ta island and Son Ca island, Nam Yet island, Truong Sa Lon island, Sinh Ton island, Ba Bau and Binh Nguyen island. The second structural block along the northeast - southwest direction includes the following islands and sandbars: Da Lat, Truong Sa island, Da Tay, Da Dong, Chau Vinh. The remaining Phan Vinh island, Toc Tan sandbar, Nui Le, Ky Van, Tham Hiem sandbar and Kieu Ngua sandbar are distributed in the third structural block. In addition, all the 3 blocks are the negative structures. In terms of geological structural boundaries: The estimated depth of the boundaries (uplifts, subduction zones, or faults,...) on Hoang Sa archipelago only reaches a maximum of 20 km. Meanwhile, that on Truong Sa archipelago is possibly over 20 km